Research Paper on Cloud Migration - Kunal Kohinkar (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The process of moving an organization's digital assets from on-premises systems to the cloud is known as cloud migration. Although cloud migration has many advantages, it also has a number of disadvantages, such as security risks, compliance issues, and vendor lock-in. This paper surveys the current writing on cloud relocation to recognize the advantages, dangers, and procedures for fruitful movement. The study employs a qualitative research design and conducts a systematic literature review on cloud migration. Academic journals, conference proceedings, and industry reports are all sources of information. The study uses thematic analysis to find the most important ideas and themes in the literature. According to the findings of the literature review, migrating to the cloud has a number of advantages, including cost savings, scalability, and agility. The study highlights the significance of careful planning and evaluation of the suitability of cloud services for various types of applications and discusses the implications of the findings for businesses considering cloud migration. The review finishes up by summing up the advantages, dangers, and techniques for fruitful cloud movement, featuring the need to address security dangers and consistence issues, and the significance of laying out clear administration and security approaches.